Margaret Cavendish, the last natural philosopher - Begley, J (2016)
This thesis uses the entirety of Margaret Cavendish's archive to present the first full account of her thought within its historical context. Living in France, the Netherlands, and England, Cavendish’s ideas were honed and in some cases prompted by her correspondences with figures who were central to the Republic of Letters, such as Constantijn Huygens, Samuel Sorbière, and Kenelm Digby. In their turn, a wide range of Cavendish’s contemporaries rigorously engaged with her publications. Bringing atomism from France to England, she encouraged Walter Charleton's translation of Pierre Gassendi's Animadversiones; Thomas Shadwell’s critique of the Royal Society in his popular satirical play, The Virtuoso, was based on The Blazing World; Arthur Annesley heavily annotated Cavendish’s De vita ... Guilielmi ducis Novo-Castrensis in preparing his own Latin history; Susan Du Verger wrote a folio-length response to Cavendish’s reflections on monasticism; and Nehemiah Grew read her medical treatise when developing his comparative anatomy. Far from being the eccentric and isolated "Mad Madge" of common repute, I recover Cavendish as one of the most prolific and philosophically informed English writers of the seventeenth century. When Cavendish's ideas have been studied in relation to those of other thinkers, she has usually been aligned with novatores, especially Thomas Hobbes and René Descartes. While these figures were "philosophers" insofar as they held undergraduate degrees, they desired to cleanse philosophy of the Aristotelian detritus of the university curriculum in which it had long been submerged. Paradoxically, I show that it was precisely because of Cavendish's lack of a formal education that she was more willing to align herself with the universities, and with the mainstream of seventeenth-century thought, than Hobbes and Descartes. Pushing back on the historiographical consensus, I show that through her career-long dialogue with editions, commentaries, and translations of ancient mythology, history, and natural philosophy, Cavendish cleaved to Aristotelian principles and categories as an antidote to the intellectual and religious turmoil of her times. In doing so, I argue that she produced the first (and last) work of traditional natural philosophy composed wholly in the English vernacular. Rather than priming her to embrace a closed and dogmatic set of philosophical precepts, this thesis underscores the inherent plurality of Aristotelian natural philosophy. The first chapter studies Cavendish's 1653 Poems, and Fancies in relation to the mythological publications of Francis Bacon and George Sandys, and the atomic writing of Pierre Gassendi and Thomas Harriot. Turning from her atomism, the second chapter discusses the material spirits of her 1653 Philosophicall Fancies and her 1655 Philosophical and Physical Opinions. It demonstrates that Cavendish’s opposition to the mathematical and mechanical corpuscles of Descartes, and her interest in the traditions of Galenic and chymical medicine, inspired this shift in her substance theory. The third chapter moves from one higher discipline to the next by studying the theological ideas of Cavendish’s 1664 Philosophical Letters. It argues that she developed a Reformed Anglican theology against the heterodox Platonic philosophy and cabalistic theology of Henry More and Joseph Glanvill. Shifting the target of her criticism, the fourth chapter finally studies how Cavendish manipulated Thomas Stanley's History of Philosophy to critique the Royal Society in her 1666 Observations Upon Experimental Philosophy and the Blazing World. Bookended by the influences of Gassendi and Thomas Stanley, Cavendish manipulated the more discursive and hermeneutic modes of Aristotelian thought to cultivate a continuum between literature as imaginative writing and literae humaniores as an embodiment of the encyclopaedia of learning. By building on methodologies not only from literary history, but also from the histories of science, philosophy, and scholarship, my work shows that Cavendish's oeuvre is one of the most powerful examples of the degree to which the seventeenth-century realms of the "new philosophy", literature, and learning were intertwined.